Effect of cooling and some treatments on the qualities of strawberry fruits - Abdullah, Uday Mohammed; Hussein, Ghaleb Nasser (Journal of agricultural, environmental and veterinary sciences, 2019)
This study was conducted at the Research Station of the college of Agriculture University of Diyala for the period from 29/10/2017 to 1/6/2018 to study the effect of cooling periods and some spraying treatments on the qualities of strawberry fruit. The experiment included two factors first included planets cooling at 4±1 and three periods (without cooling, cooling for one week, and cooling for two weeks), The second factor was using chelated iron spray with a concentration at 75mg.L-¹ and nano-Iron spray with a concentration at 75mg.L-¹ and calcium chloride spraying at a concentration at 0.5g. L-¹carbonate nanoparticles at a concentration at 2g. L-¹ control treatment was sprayed with distilled water. The experiment conducted using Randomized Complete Block Design (RCBD) with four replications. The results were analyzed using the SAS statistical program (2003). The differences between treatment were compared by using the Duncan multiple Range test at 0.05 level. The level of cooling for two weeks was significant superior in number of fruits, the average weight of the fruit, the highest hardness of fruits, the percentage of TSS. The results showed significant superiority of nano-Iron spraying on most of the studied traits, which significantly increased the number of flowers, number of fruit and gave highest TSS. The results showed the superiority of the spraying of calcium carbonate nanoparticles on the average of weight of fruit, the highest hardness of fruits. The interaction treatment between cooling for two weeks and spraying of calcium carbonate nanoparticles gave significantly increased the average number of fruits, the average fruit weight and the highest hardness of fruits.